ABDURAUF FITRAT AND HIS PLACE IN HISTORY - Hazratova Zebiniso (Web of Journals Publishing, 2025)
This article examines Fitrat’s efforts to awaken the nation through his educational, literary, and social activities. As a leading figure of the Jadid movement, he promoted ideas aimed at raising public consciousness, developing modern education, and restoring national identity.
Keywords: Jadidism, Fitrat, Mijmar, Turkey, education, national awakening, reform, literature, charity society, Fayzulla Khodjaev, Sadoi Turkiston.